TikTok Narratology, Health Belief System and Sexual Health Awareness among Students of Akwa Ibom State University - Udoudom, Uduak (Journal of Health Science and Medical Therapy, 2025)
This study investigated the influence of TikTok narratology and students' health belief systems on sexual health awareness among Akwa Ibom State University students. The research utilised the Health Belief Model as its theoretical framework. The study employed a cross-sectional survey design, with a sample size of 370 participants drawn from the population of 10,200 students using the Krejcie and Morgan formula. A structured questionnaire was employed to gather data, which was analysed to determine students' knowledge, perception, and practices regarding reproductive and sexual health information shared on TikTok platform. Findings demonstrated that TikTok increased students' understanding of reproductive and sexual health issues, with many participants finding its content relatable, engaging, and informative. However, participants evaluated content credibility primarily through its alignment with their existing health beliefs. While TikTok campaigns by organisations such as the Society for Family Health (SFH) and the Association for Reproductive and Family Health (ARFH) effectively shaped participants' knowledge, attitudes, and practices, doubt existed when the content contradicted cultural or personal health beliefs. Additionally, the combination of easy accessibility with innovative narrativity enabled TikTok to become an effective health communication channel, but it needed enhancement to adapt sensibly to different cultural belief systems. The study concluded that students' health belief systems determine how effectively TikTok could spread sexual health information, though the platform is a valuable tool for sexual health information dissemination. It is recommended that health educators and campaign organisers develop culturally sensitive and credible content that aligns with student's needs while working with trusted organisations to integrate TikTok into broader health awareness programmes. Communicators were also urged to support digital health campaigns to enhance their reach and impact.